The Role of the Surgeon and Transurethral Resection in the Treatment of Superficial Bladder Cancer - Alan M. Nieder; Murugesan Manoharan (The Scientific World Journal)
Non-muscle invasive bladder cancers are a heterogeneous group of cancers whose spectrum includes low grade Ta lesions and high-grade T1 lesions. Accurate staging and grading during initial evaluation and TUR ensures appropriate treatment and prevents the risk of understaging. TUR should be ideally performed under spinal anesthesia, with a continuous flow video resectoscope to maintain a stable bladder capacity, and a video monitor. The entire bladder must be visualized, with both 30- and 70-degree lenses, and all abnormal areas must be resected, with separate biopsies from each tumor's base. Repeat TUR is recommended for all high grade tumors and T1 tumors, especially if muscle was not present in the initial specimen. Immediate instillation of single dose chemotherapy agents following TUR is highly recommended to reduce the risk of tumor recurrences.